2012
DOI: 10.1371/journal.pone.0048015
|View full text |Cite
|
Sign up to set email alerts
|

Crystal Structures of Two Transcriptional Regulators from Bacillus cereus Define the Conserved Structural Features of a PadR Subfamily

Abstract: PadR-like transcriptional regulators form a structurally-related family of proteins that control the expression of genes associated with detoxification, virulence and multi-drug resistance in bacteria. Only a few members of this family have been studied by genetic, biochemical and biophysical methods, and their structure/function relationships are still largely undefined. Here, we report the crystal structures of two PadR-like proteins from Bacillus cereus, which we named bcPadR1 and bcPadR2 (products of gene … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
34
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(35 citation statements)
references
References 41 publications
0
34
0
Order By: Relevance
“…In addition, protein crystallography, fusion of AphA to the DNA binding domain of LexA, and the use of crosslinking reagents showed that AphA protein forms a dimer (18,48). Obviously, members of the PadR-like proteins form dimers due to their C-terminal domain, which is a coiled-coil leucine zipper-like structure (23). Despite this structural resemblance, the already-known PadR-like regulators function in different regulatory pathways.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, protein crystallography, fusion of AphA to the DNA binding domain of LexA, and the use of crosslinking reagents showed that AphA protein forms a dimer (18,48). Obviously, members of the PadR-like proteins form dimers due to their C-terminal domain, which is a coiled-coil leucine zipper-like structure (23). Despite this structural resemblance, the already-known PadR-like regulators function in different regulatory pathways.…”
Section: Discussionmentioning
confidence: 99%
“…Subfamily 1 has a C-terminal domain of 80 to 90 residues, such as AphA from Vibrio cholerae (18), LadR from Listeria monocytogenes (19), and PadR from Pediococcus pentosaceus, Lactobacillus plantarum, or Bacillus subtilis (11,20,21). The proteins of subfamily 2 have a shorter C-terminal domain than subfamily 1 and contain 20 to 30 residues, such as LmrR from Lactococcus lactis (22) as well as Bacillus cereus PadR1 (bcPadR1) and bcPadR2 (23). Apart from their structures, physiological characteristics of the PadR, AphA, and LmrR regulators were intensively studied (21,(24)(25)(26).…”
mentioning
confidence: 99%
“…Other members of this protein family are shown to regulate diverse processes, including multidrug resistance (53-55), virulence (56), and cellular metabolism (57,58). Many PadR family regulators repress the transcription of the target genes by binding to specific sequences of the promoter regions with a conserved N-terminal winged helix-turn-helix domain and thereby blocking the promoter-RNA polymerase interactions in the absence of inducers (e.g., phenolic acid and antibiotic) (46,59). Transcriptional derepression occurs when the regulator "falls off" the target DNA sequence after binding to the cognate inducers (e.g., phenolic acid and other toxic compounds) (46,59).…”
Section: Discussionmentioning
confidence: 99%
“…Many PadR family regulators repress the transcription of the target genes by binding to specific sequences of the promoter regions with a conserved N-terminal winged helix-turn-helix domain and thereby blocking the promoter-RNA polymerase interactions in the absence of inducers (e.g., phenolic acid and antibiotic) (46,59). Transcriptional derepression occurs when the regulator "falls off" the target DNA sequence after binding to the cognate inducers (e.g., phenolic acid and other toxic compounds) (46,59). The four copies of the B. subtilis PadR repressor are predicted to bind to four different sequence motifs in each promoter sequence of the phenolic acid response gene locus in the absence of phenolic acid (inducer) (48).…”
Section: Discussionmentioning
confidence: 99%
“…1). YqjI is a member of the PadR family of transcriptional regulators but contains an additional N-terminal extension that is rich in potential metal-binding residues (such as Cys, His, and Glu) (7,8). Apo-YqjI is purified as both a monomer and in an oligomeric form.…”
mentioning
confidence: 99%